A Practical Approach to Molecular Cloning - Das, Satarupa; Das, Biswadip (Bentham Science Publishers, 2025)
This laboratory manual is designed to introduce beginner level researchers to the essential experimental techniques of molecular cloning. With a strong focus on hands-on protocols and a clear, cloning-centric framework, the book simplifies complex methods while building a strong foundation in molecular biology. Across eight structured chapters, the manual initially covers topics such as laboratory safety and fundamental skills, then progresses through microbiological techniques, DNA isolation and purification, DNA analysis, recombinant DNA construction to clone identification. The final chapter includes detailed appendices outlining standard reagent compositions and preparation methods. Special emphasis is placed on the rationale behind each procedure, making the learning process both practical and conceptually grounded. Key features: Explains experimental protocols with step-by-step clarity Gives rationale and mode of action behind each procedure Emphasizes critical steps through italicized notes and tips Provides special information panels for deeper contextual knowledge Include comprehensive appendices for reagent preparation and reference